UJI PREFERENSI TUMBUHAN INANG BEBERAPA POPULASI KUMBANG LEMBING Epilaehna. aff. emarginata (COLEOPTERA; COCCINELLIDAE; EPILACHNINAE) - Sih Kahono; Liliek Endang Pujiastuti; Naoyuki Fujiyama; Susumu Nakano (BERITA BIOLOGI, 2002)
Epilaehna sp. aff. emarginata had been considered as a specialist on Mikania micrantha (Compositae). However, recently its oceurrence on Leucas lavandulifolia (Labiatae) was reported. Preliminary field observations of some beetle populations showed that they had different on the host plant utilizations. However, the result was not sufficient to interpret the food preference of the beetles. These experiments weremade in order to clarify those previous observations.Experiments on adult food preference was investigated under uncontrolled room conditions.Four beetle populations (Bogor, Cibinong, Klaten and Malang) were subjected to choice tests offering Mikania micrantha (Compositae) and Leucas lavandulifolia. These experiments indicated that individual beetle has similar trend on food preference within each population. Bogor and Cibinong populations preferred to feed on both M. micrantha and L. lavandulifolia while. Klaten and Malang populations preferred exclusively on L. lavandulifolia. The populations showed different food preferences on the different geographical conditions of Java.